Pertimbangan Konsumen Dalam Membeli dan Membaca Surat Kabar di Jawa Timur dengan Analisis Faktor - Lilik Indrawati (BIP's JURNAL BISNIS PERSPEKTIF, 2010)
Newspaper business competition in East Java makes many newspapers are offered to public. This condition make the company must know customer's want and need, by improving quality of factors in a newspaper, so it will attract customer's interest to buy and read it. There are 12 variables which are classified to 4 factors which influence the customer in buying ang reading Jawa Pos newspapers in East Java, such as: (1) Service factor with composite variable which consist of reader's feedback, display design, reward, compensation voucher for late delivery, easy to get and delivery on time; (2) Quality factor with composite variable which consist of brand image, up to date news, printing quality and numbers of page; (3) Contents factor with composite variable: creative ond inovation news contents; (4) Habit factor with composite variable: family habit. With these factors in buying and reading newspaper above, factor analysis calculation is used as marketing tools for Jawa Pos newspaper in East Java for knowing ang taking action for the company improvement.